Dukungan Sosial Guna Pemenuhan Hak Sosial Ekonomi Bagi Klien Pemasyarakatan di Balai Pemasyarakatan Kelas I Jakarta Pusat. - Setyani, Dina; Nugroho, Fentiny (Jurnal Ilmu Kesejahteraan Sosial, 2020)
This study aims to describe social support in order to fulfill the socio-economic rights of correctional clients. The socio-economic rights are the second generation of human rights groups which focus on the welfare aspect. Assistance as a form of social approach to achieve welfare based on human rights, where clients can identify their own needs, so as to minimize human rights violations and have the opportunity to function socially and live well. The existence of social support from the nearest environment makes the client able to adapt back to the community and be able to develop his potential. The research method is qualitative with descriptive design. Data collection techniques with literature study, in-depth interviews and observations, while the informants in this study were seven adult clients who had worked, two family members of the client, one community leader, and three community mentors. The results of the study illustrate that clients who have worked get good social support from their families and social mentors in the form of support, advice and information that can help clients solve any problems that hinder their potential development. Social support from the community towards the client is still lacking because there is a sense of community indifference towards the fulfillment of the client's economic rights. The community around the client's residence is limited to fulfilling the client's social rights by re-accepting the existence of the client in the environment, but has not paid more attention to the fulfillment of his economic rights. The need for the role of family and community counselors in taking a special approach to society in order to increase community support and remove the negative stigma toward clients, so that the client's socio-economic rights are fulfilled properly.